Pertimbangan Hakim Pengadilan Agama Curup Terhadap Izin Poligami Suami Yang Tidak Memenuhi Syarat Poligami Dalam Hukum Positif Di Indonesia - Oktasari, Orin (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Consideration Of Judge In Religious Court Of Curup On Permitting The Polygamy Of Husband Who Do Not Eligible For Polygamy In According To Indonesia’s Positive Law. Religious Court in its task of giving a decision on the application for polygamy, guided by the rules, namely Law No. 1 of 1974, Government Regulation No. 9 of 1975 and the Compilation of Islamic Law. Examples of cases that occurred in 2013 in case No. 142 / Pdt.G / 2013 / PA CRP.and Case Number: 542 / Pdt.G / 2013 / PA CRP. This paper is discussing a review of Islamic law against the decision of the permission for polygamy who do not eligible, consideration of the judge in deciding the permission of polygamy and the power of law permits polygamy who are not eligible. This type of research is normative empirical, and data analysis with qualitative methods. Collecting data using techniques of documentation, interviews and observation. The results of this study indicate first, in Islamic law, the decision on case number 142 / Pdt.G / 2013 / PA CRP and case number 542 / Pdt.G / 2013 / PA CRP were determined by a panel of judges have compatibility with the context of ijtihad, and the results of its legal can be carried out without shutting down the previous law. The result of this decision is a form to fill a legal vacuum. Then, the Religious Court judges of Curup perform legal breakthrough (contralegem), because it does not apply Article 4 (2) of Law No. 1 of 1974 in the examination of the case. So the legal reasoning used by the judge in deciding the case number 142 / Pdt.G / 2013 / PA CRP and case number 542 / Pdt.G / 2013 / PA CRP is weak because it does not correspond to the reasons for the permissibility of polygamy in the legislation.